Factors affecting investment decision in Indonesia: Mediating role of intention to invest - Maulana, Hartomi; Ulya, Alfina Zein Syarifa; Syahruddin, Syahruddin; Abadi, M. Kurnia Rahman; Hastuti, Ely Windarti; Harahap, Soritua Ahmad Ramdhani (Jurnal Ekonomi & Keuangan Islam, 2025)
Purpose – This study examines the effects of digital financial literacy and cognitive ability on investment decisions. The study also investigates how the intention to invest mediates the relationship between digital financial literacy, cognitive ability, and Sharia investors’ decisions.Methodology – The methodology used in this study is a quantitative approach with probability sampling techniques of the cluster sampling method. The sample determination was performed using the Slovin formula. As a result, 400 respondents from seven major cities in East Java were obtained. Partial Least Square - Structural Equation Modelling (PLS-SEM) was used as an analysis technique.Findings – The results indicate that digital financial literacy and cognitive ability have a significant effect on investment decisions. Investment intention has been proven to act as a mediating variable linking digital financial literacy and cognitive ability with investment decisions.Implications – It is important for investors to have a good level of digital financial literacy and adequate cognitive abilities to improve investment decision-making. Investment intention is an important factor mediating the influence of both variables on investment decisions.Originality – This study contributes significantly to the comprehension of the factors that influence investment decisions, as well as the contribution of investment intention to the process.